(untitled) (Journal of Partial Differential Equations, 2020)
" In this paper we deal with the self-similar singular solution of the p-Laplacian evolution equation u_t = div(|2207|^p-22207u) - |2207u|^q for p > 2 and q > 1 in R^n 00d7 (0, 221e). We prove that when p > q + n\/(n + 1) there exist self-similar singular solutions, while p 2264 q+n\/(n+1) there is no any self-similar singular solution. In case of existence, the self-similar singular solutions are the self-similar very singular solutions, which have compact support. Moreover, the interface relation is obtained."